2002
DOI: 10.1016/s0008-6363(02)00281-x
|View full text |Cite
|
Sign up to set email alerts
|

An aldosterone synthase gene variant is associated with improvement in left ventricular ejection fraction in dilated cardiomyopathy

Abstract: A CYP11B2 gene variant predicts the variable improvement in LV ejection fraction that occurs subsequent to initiating medical therapy in IDC. These data suggest a role for the aldosterone synthase locus in regulating the progression of heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 18 publications
2
36
0
1
Order By: Relevance
“…11 The genotype distributions among the controls of all studies were consistent with HWE except for one study. 11 Of the six retrospective studies, four papers used population-based controls, [11][12][13][14] and two studies of one paper used hospital-based controls. 15 The study by Goldbergova et al 12 used the mismatch method, and the other studies used polymerase chain reaction/restriction fragment length polymorphism for genotyping.…”
Section: Resultsmentioning
confidence: 59%
“…11 The genotype distributions among the controls of all studies were consistent with HWE except for one study. 11 Of the six retrospective studies, four papers used population-based controls, [11][12][13][14] and two studies of one paper used hospital-based controls. 15 The study by Goldbergova et al 12 used the mismatch method, and the other studies used polymerase chain reaction/restriction fragment length polymorphism for genotyping.…”
Section: Resultsmentioning
confidence: 59%
“…Most studies did not find an association between the ACE polymorphism and heart failure secondary to ischemic and/or dilated cardiomyopathy in 1506 Caucasian, [23][24][25][26] 287 Chinese, 27 281 Japanese, 28 and 724 black South African subjects. 29,30 Hence, it seems unlikely that susceptibility to ischemic or idiopathic dilated cardiomyopathy in the general population is associated with the ACE I/D polymorphism.…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…Candy et al 30 found an association between DD genotype and reduced cardiac function and increased cavity size in South African patients with cardiomyopathy, whereas others did not. 29 The first study on the ACE polymorphism and hypertrophic cardiomyopathy found an excess of DD genotype in Caucasian patients, especially in families with a history of sudden cardiac death. 36 Other studies have since then confirmed the higher frequency of DD genotype in hypertrophic cardiomyopathy in white and Japanese patients.…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
See 2 more Smart Citations